2022
DOI: 10.1007/s00405-022-07546-w
|View full text |Cite
|
Sign up to set email alerts
|

An iOS-based VoiceScreen application: feasibility for use in clinical settings—a pilot study

Abstract: Objectives To elaborate the application suitable for smartphones for estimation of Acoustic Voice Quality Index (AVQI) and evaluate its usability in the clinical setting. Methods An elaborated AVQI automatization and background noise monitoring functions were implemented into a mobile “ VoiceScreen” application running the iOS operating system. A study group consisted of 103 adult individuals with normal voices ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
8
0
2
Order By: Relevance
“…The multivariate structures of the VWI, AVQI, and ABI, on the other hand, depend on a linear regression model which incorporates pertinent acoustic parameters; they consist of both continuous speech and sustained vowel sounds in the acoustic evaluation, and the processing of signals employs freeware Praat algorithms, and can thus be standardized and made automated. This has already been realized in several applications available for AVQI estimation: VoiceEvalU8 [ 48 ], A Comprehensive Application for Grading Severity of Voice [ 29 ], VoiceScreen, version 4.4.22 [ 49 ], and ABI assessment: VOXplot, version 2.0 [ 50 ]. As a result, the registration of the AVQI, ABI, and VWI as an “ecologically valid” MAVI may be readily accomplished using specific programs, even without the presence of trained staff, allowing individuals to self-assess their voice quality.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate structures of the VWI, AVQI, and ABI, on the other hand, depend on a linear regression model which incorporates pertinent acoustic parameters; they consist of both continuous speech and sustained vowel sounds in the acoustic evaluation, and the processing of signals employs freeware Praat algorithms, and can thus be standardized and made automated. This has already been realized in several applications available for AVQI estimation: VoiceEvalU8 [ 48 ], A Comprehensive Application for Grading Severity of Voice [ 29 ], VoiceScreen, version 4.4.22 [ 49 ], and ABI assessment: VOXplot, version 2.0 [ 50 ]. As a result, the registration of the AVQI, ABI, and VWI as an “ecologically valid” MAVI may be readily accomplished using specific programs, even without the presence of trained staff, allowing individuals to self-assess their voice quality.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the suitability of smartphone microphones for capturing voice recordings, even in the presence of ambient noise, and their capability to successfully record lung sounds, making auscultation feasible, are widely demonstrated in the literature [ 4 , 5 ]. Moreover, they have been found to be adequate for the digitization of pathologic voices, making them valuable for clinical voice research [ 6 ]. The high performance of smartphone microphones has been further proven in studies showing how they outperform standard external microphones in recording and analyzing normal and dysphonic voices [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pitch perturbation (local jitter and periodic standard deviation) and the harmonics-to-noise ratio from Dejonckere and Lebacq appear to be the most reliable acoustic metrics. The study on the end-user mobile app "VoiceScreen" also demonstrated an accurate and robust method for measuring voice quality and the potential to be used in clinical settings as a sensitive assessment of voice alterations throughout the results of phonosurgical treatment [15].…”
Section: Introductionmentioning
confidence: 99%